2021
DOI: 10.1270/jsbbs.20089
|View full text |Cite
|
Sign up to set email alerts
|

Translation of continuous artificial selection on phenotype into genotype during rice breeding programs

Abstract: Understanding genetic diversity among local populations is a primary goal of modern crop breeding programs. Here, we demonstrated the genetic relationships of rice varieties in Hokkaido, Japan, one of the northern limits of rice cultivation around the world. Furthermore, artificial selection during rice breeding programs has been characterized using genome sequences. We utilized 8,565 single nucleotide polymorphisms and insertion/deletion markers distributed across the genome in genotype-by-sequencing for gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The analysis implements a clustering method similar to that in the population program ADMIXTURE (Alexander et al, 2009). The genomic data for Japanese, Chinese and U.S. weedy rice and Japanese cultivated rice, which were obtained in the previous studies (Arai‐Kichise et al, 2011; Arai‐Kichise et al, 2014; Fujino et al, 2021; Imaizumi et al, 2021; Li et al, 2017; Qiu et al, 2017; Tanaka et al, 2020; Wei et al, 2016; Xu et al, 2011), were retrieved from the DRA/DDBJ repository. The raw paired‐end reads were first trimmed with Trimmomatic version 0.38 (Bolger et al, 2014) with the parameters “ILLUMINACLIP:2:30:10 LEADING:20 TRAILING:20 SLIDINGWINDOW:10:20 MINLEN:30”.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis implements a clustering method similar to that in the population program ADMIXTURE (Alexander et al, 2009). The genomic data for Japanese, Chinese and U.S. weedy rice and Japanese cultivated rice, which were obtained in the previous studies (Arai‐Kichise et al, 2011; Arai‐Kichise et al, 2014; Fujino et al, 2021; Imaizumi et al, 2021; Li et al, 2017; Qiu et al, 2017; Tanaka et al, 2020; Wei et al, 2016; Xu et al, 2011), were retrieved from the DRA/DDBJ repository. The raw paired‐end reads were first trimmed with Trimmomatic version 0.38 (Bolger et al, 2014) with the parameters “ILLUMINACLIP:2:30:10 LEADING:20 TRAILING:20 SLIDINGWINDOW:10:20 MINLEN:30”.…”
Section: Methodsmentioning
confidence: 99%
“…Within 60 years in rice breeding programs in Hokkaido, from the start of the programs in 1915, awn was completely lost on both phenotype and genotype on RAE1 and RAE2. During rice breeding programs in Hokkaido, genomic changes have been characterized (Fujino et al 2015(Fujino et al , 2021Shinada et al 2014). Our ndings of rae1 gene ows and multiple rae2 alleles clearly demonstrated that rice breeding programs could generate genetic diversity among self-pollinating plant.…”
Section: Discussionmentioning
confidence: 71%
“…Two accessions (JRC21 and JRC40) were excluded from this study due to the contradictions in genotype and degree of nucleotide polymorphism. Fourth, rice varieties from Hokkaido were used, denoted as 20V, accessible in the DDBJ BioProject database under accession numbers DRA008447, DRA006623, and DRA006604, respectively (Fujino et al 2015(Fujino et al , 2018(Fujino et al , 2021Fujino and Ikegaya 2020). The genome sequences of all varieties were assembled from high-throughput sequencing short reads.…”
Section: Genome Sequencesmentioning
confidence: 99%